Plastic changes in amygdala subregions by voluntary running contribute to exercise-induced hypoalgesia in neuropathic pain model mice. (December 2020) - Kami, Katsuya; Tajima, Fumihiro; Senba, Emiko
Physical exercise has been established as a low-cost, safe, and effective way to manage chronic pain, but exact mechanisms underlying such exercise-induced hypoalgesia (EIH) are not fully understood. Since a growing body of evidence implicated the amygdala (Amyg) as a critical node in emotional affective aspects of chronic pain, we hypothesized that the Amyg may play important roles to produce EIH effects. Here, using partial sciatic nerve ligation (PSL) model mice, we investigated the effects of voluntary running (VR) on the basal amygdala (BA) and the central nuclei of amygdala (CeA). The present study indicated that VR significantly improved heat hyperalgesia which was exacerbated in PSL-Sedentary mice, and that a significant positive correlation was detected between total running distances after PSL-surgery and thermal withdrawal latency. The number of activated glutamate (Glu) neurons in the medal BA (medBA) was significantly increased in PSL-Runner mice, while those were increased in the lateral BA in sedentary mice. Furthermore, in all subdivisions of the CeA, the number of activated gamma-aminobutyric acid (GABA) neurons was dramatically increased in PSL-Sedentary mice, but these numbers were significantly decreased in PSL-Runner mice. In addition, a tracer experiment demonstrated a marked increase in activated Glu neurons in the medBA projecting into the nucleus accumbens lateral shell in runner mice. Thus, our results suggest that VR may not only produce suppression of the negative emotion such as fear and anxiety closely related with pain chronification, but also promote pleasant emotion and hypoalgesia. Therefore, we conclude that EIH effects may be produced, at least in part, via such plastic changes in the Amyg.